Toxicity and radiation dosimetry studies of the serotonin transporter radioligand [(18) F]AFM in rats and monkeys - Huang, Ya-Yao (EJNMMI Res, 2014)
BACKGROUND: [(18) F]AFM is a potent and promising PET imaging agent for the serotonin transporter. We carried out an acute toxicity study in rats and radiation dosimetry in monkeys before the translation of the tracer to humans. METHODS: Single- and multiple-dose toxicity studies were conducted in Sprague–Dawley rats. Male and female rats were injected intravenously with AFM tartrate as a single dose of 98.7 or 987 μg/kg (592 or 5,920 μg/m(2), 100× or 1,000× the proposed human dose of 8 μg, respectively) on day 1 or as five consecutive daily doses of 98.7 μg/kg/day (592 μg /m(2)/day, 100× human dose, total dose 493.5 μg/kg). PET/CT scans were performed in four Formosan rock monkeys (two males and two females, each monkey scanned twice) using a Siemens BIOGRAPH scanner. After injection of [(18) F]AFM (88.5 ± 20.3 MBq), a low-dose CT scan and a series of eight whole-body PET scans in 3-D mode were performed. Time-activity data of source organs were used to calculate the residence times and estimate the absorbed radiation dose using the OLINDA/EXM software. RESULTS: In the rats, neither the single dose nor the five daily doses of AFM tartrate produced overt adverse effects clinically. In the monkeys, the radiation doses received by most organs ranged between 8.3 and 39.1 μGy/MBq. The osteogenic cells, red marrow, and lungs received the highest doses of 39.1, 35.4, and 35.1 μGy/MBq, respectively. The effective doses extrapolated to male and female adult humans were 18.0 and 18.3 μSv/MBq, respectively. CONCLUSIONS: Toxicity studies in Sprague–Dawley rats and radiation dosimetry studies in Formosa rock monkeys suggest that [(18) F]AFM is safe for use in human PET imaging studies. TRIAL REGISTRATION: IACUC-12-200.